2018
DOI: 10.2147/copd.s170555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of YuPingFeng granules on acute exacerbations of COPD: a randomized, placebo-controlled study

Abstract: PurposeRecurrence of acute exacerbations has a major impact on patients with COPD. Therefore, effective prevention and treatment of exacerbation is crucial in the management of COPD, especially for patients with moderate to severe disease. This study evaluated the effectiveness of YuPingFeng granule administration in preventing exacerbation and improving symptom score, as well as its long-term (1 year) safety profile, in patients with COPD.Patients and methodsThis was a randomized, double-blind, parallel, plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Iwasaki et al (34)(35)(36). In the majority of the studies, crude drugs added to the conventional therapy prevented recurrence of acute exacerbation.…”
Section: Nonementioning
confidence: 99%
“…Iwasaki et al (34)(35)(36). In the majority of the studies, crude drugs added to the conventional therapy prevented recurrence of acute exacerbation.…”
Section: Nonementioning
confidence: 99%
“…There are four groups with two variables in this trial—TCM treatment and systemic glucocorticoid treatment. Therefore, according to primary endpoints collected from previous trial [ 34 , 41 ], we choose the maximum sample size needed, as calculated by two way on http://www.powerandsamplesize.com (Table 2 ). At the 5% significance level, a total of 67 patients per group will be required for a 2-group, 1-sided calculation to achieve 80% power and the differences of 10.30 ± 6.31 and 12.95 ± 5.99 in CAT mean score between the TCM treatment group and placebo group (Table 5 ).…”
Section: Interventionsmentioning
confidence: 99%
“…Hopefully, traditional Chinese medicines (TCM) can expand COPD treatment in terms of syndromic difference, also called Zheng [ 29 ]. Not only has TCM alleviated symptoms such as coughing, shortness of breath, and sputum for thousands of years, but also has demonstrated its efficacy and safety [ 30 34 ]. However, there are rarely studies focused on COPD patients during the acute exacerbation period, most of them focused on the relatively stable period.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of clinical trials, such as TORCH [6], UPLIFT [7], INSPIRE [8], and small-dose-theophylline [9], have all confirmed that Western medicine could decrease the mortality rate and the risks of AE for stable COPD patients and slow down the annual decline of lung function. Recent study has also shown that treating patients with stable COPD is positive for managing the disease and preventing its exacerbation [10] and progression [11]. The medication can alleviate the clinical symptoms of COPD, but it cannot stop or reverse the decline of lung function, and some important problems caused by Western medicine need to be solved, such as side effects of medicine and pneumonia [6, 8].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above deficiency, more relevant researches have been conducted, which have obtained some certain achievements. Evidences indicate that TCM has some positive effects in the treatment of stable COPD, which could be showed in clinical trials [10, 12] and animal experiments [13–15]. It could bring a reduction of clinical symptoms and disease progression.…”
Section: Introductionmentioning
confidence: 99%